IMPORTANCE OF GHRITA IN OLD AGE - Rajendra H.M. (International Journal of Applied Ayurved Research, 2016)
Aged state is a condition in which decline of functional capacity; physical, mental or both has become manifest, measurable and adoptively significant. Currently, population ageing is oc-curring at a rapid rate particularly in the developing regions of the world like India. Conse-quently more and more people are surviving into old age, having increased life expectancy. Hence a multi dimensional approach is essential to provide a good quality life to older people. It comprises not only curative but also non-curative methods of care such as preventive, rehabilitative and terminal care. In Ayurveda, Ghrita is indicated in old age being best among all the Snehas and Vayasthapana. Ghrita plays an important role in controlling vata dosha, which is the main causative factor of old age. The presence of Mahabhutas and Gunas in Ghrita helps to maintain the health of old age persons from deterioration. Being best among all the Snehas and Vayasthapana, maintains the normal functions of Doshas, Dhatus, Malas and adds to the essence of Ojas. Hence Ghrita is considered as par excellence and drug of choice in old age.